Early Faculty and Staff (Institutional Knowledge at Singapore Management University, 1999)
Faculty and staff working on the start-up of Singapore Management University. The picture was taken on 2 September 1999 at the university’s first offices at Wah Chang House on Upper Bukit Timah Road. The team is gathered beside the three-dimensional model of SMU's proposed city campus on the occasion of President Janice Bellace's birthday.